2016
DOI: 10.1002/jcad.12103
|View full text |Cite
|
Sign up to set email alerts
|

Counselors' Social Class and Socioeconomic Status Understanding and Awareness

Abstract: Nine licensed professional counselors participated in semistructured interviews designed to reveal their awareness and understanding about social class and socioeconomic status (SES). Findings suggest that participants' descriptions of social class and SES often are incongruent with how they use the terms, and their awareness and understanding may be limited because of developmental factors, indicating potential clinical liabilities. The authors suggest that counselors should develop stronger social class cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The purpose of the study associated with the findings reported in this article was to describe counselors' social class and SES understanding and awareness. To date, one study exists on this topic (Cook & Lawson, 2016). Substantial findings emerged during the course of the study, specifically the ways in which participants described social class and SES and how they operationalized these terms (Cook & Lawson, 2016), and the findings related to classism reported in this article.…”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…The purpose of the study associated with the findings reported in this article was to describe counselors' social class and SES understanding and awareness. To date, one study exists on this topic (Cook & Lawson, 2016). Substantial findings emerged during the course of the study, specifically the ways in which participants described social class and SES and how they operationalized these terms (Cook & Lawson, 2016), and the findings related to classism reported in this article.…”
Section: Literature Reviewmentioning
confidence: 87%
“…The literature reviewed demonstrates that social class and SES bias and classism can manifest in multiple ways (Smith et al, 2013;Smith et al, 2011), and that counselor belief systems about social class can contain inherent biases, many of which the counselor may be unaware and can impact the counseling relationship negatively (Balmforth, 2009). Multicultural training can have a positive impact on counselors, yet many do not receive significant training about social class and SES (Toporek & Pope-Davis, 2005), which may be due to a dearth of research in counselor education about counselors' understanding and awareness about social class (Cook & Lawson, 2016). The purpose of the study associated with the findings reported in this article was to describe counselors' social class and SES understanding and awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social class is a complex construct associated with one’s ranked place in the world relative to others based on economic and social factors (Cook & Lawson, 2016). We use the following definition: Social class is a subjective identity dimension composed of discrete socioeconomic status (SES) variables (i.e., income, education, and occupation) that combine with additional factors, such as resources, location, shared and individual experiences, and perceived status, that shape attitudes, beliefs, worldviews, values, and behaviors (Cook & Lawson, 2016; Liu, Soleck, Hopps, Dunston, & Pickett, 2004). To identify social class as an identity dimension, people use many descriptors and terms that may vary by person or group (e.g., poor, blue collar, upper class, middle class, lower class, working poor, upper crust, elite, owning class, ruling class, working class).…”
mentioning
confidence: 99%
“…To identify social class as an identity dimension, people use many descriptors and terms that may vary by person or group (e.g., poor, blue collar, upper class, middle class, lower class, working poor, upper crust, elite, owning class, ruling class, working class). In addition, people often conflate social class and SES (Cook & Lawson, 2016). Although SES is necessary to defining and understanding social class, social class is not SES in and of itself (Cook & Lawson, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation